Władysław Tatarkiewicz in the Works of Czesław Głombik - Mróz, Tomasz (Folia Philosophica, 2022)
The paper aims to present the most important works of Czesław Głombik, in which he analysed the philosophical and historical-philosophical legacy of his university teacher, Władysław Tatarkiewicz. It was thanks to Tatarkiewicz, inter alia, that Głombik undertook research on the history of Polish philosophy. Głombik’s most important areas of interest in the history of philosophy and his research methods are discussed on the basis of his works devoted to Tatarkiewicz. The paper is enriched with personal memories and correspondence.